Pengaruh Sstem Informasi Akuntansi (SIA) Terhadap Kinerja Pegawai Dengan Budaya Organisasi Sebagai Variabel Intervening (Studi Empiris Pada Komisi Pemilihan Umum Daerah (KPUD) Kabupaten Karawang) - Nanu Hasanuh (Accounthink, 2016)
Accounting information system quality and organization culture associated with employee performance. Good accounting information system quality and organization culture perceived by employees can improve employee performance. System and values in organization will improve employee performance so that will impact on increasing overall business performance. This research was conducted at Kantor Pemilihan Umum Daerah (KPUD) Kabupaten Karawang. This research aims to analyze the influence of accounting information system moderated by organization culture to employee performance. Independent variable in this research is accounting information system quality, moderating variable is organization culture, and dependent variable is employee performance. Analyses used involve validity test, reliability test, classic assumption test, and hypothesis testing. Analyses result show that accounting information system quality has positive influence to employee performance and organization culture mediate accounting information system quality to employee performance.